An Attempt to Relate Consolidation Properties: A Case Study in Baghdad Cohesive Soil - Abbas Jawad Al-Taie; Bushra S. Al-Busoda (International Journal of Advances in Applied Sciences, 2013)
The main focus of this study is on the soil properties (preconsolidation pressure (Pc), and overconsolidation ratio (OCR)), that are critical in the determination of the settlement behavior of the structure. Prior knowledge of these properties, even approximate values, will be assets during the planning stages to determine the suitability of structure site. Conducting laboratory tests for the determination of (Pc) will be costly both in terms of time and money. In the present study a specific empirical correlation models are proposed to estimate the (Pc) and (OCR) of undisturbed cohesive soil of Baghdad city using large number of consolidation data. The (Pc) and (OCR) are dependent variables and are treated as functions of natural void ratio (eo), natural moisture content (wo), total unit weight (gt) , dry unit weights (gd), and overburden pressure (Po) which are termed as independent variables. The regression analysis revealed that (eo) and (Po) yielded sufficiently reliable correlation to estimate (Pc). Also, a good estimation was obtained for (OCR